أثر الضغوط التضخمية على سياسة الإنفاق العام في الجزائر في الفترة 2000-2019 - سحنون, عقبة; حشوف, بسمة (جامعة الوادي - University of Eloued, 2022)
ملخص: تعتبر تأثيرات الضغوط التضخمية من الدراسات الاقتصادية التي حظيت باهتمام كبير، سواء من طرف السلطات النقدية أو من طرف الباحثين الاقتصاديين خصوصا في الآونة الأخيرة، لذا ارتأينا من خلال ورقتنا البحثية هاته تسليط الضوء على كيفية تأثير الضغوط التضخمية خاصة على سياسة الانفاق العام في الجزائر، وسعيا لمعرفة ذلك اعتمدنا على المنهج الوصفي لتحديد مفاهيم التضخم وكذا النفقات العامة، وعلى المنهج التحليلي للإلمام بأسباب الضغوط التضخمية في الجزائر، وعلى المنهج القياسي باستخدام برنامج الspss والذي توصلنا من خلاله على أنه هناك علاقة قوية بين الإنفاق العام وكل من الكتلة النقدية ومعدلات التضخم، أي أن التغيرات التي تحدث في الكتلة النقدية وفي معدلات التضخم تؤثر بطريقة مباشرة على التغيرات الحادثة في الإنفاق العام. Abstract: The effects of inflationary pressures are among the economic studies that have received considerable attention both from monetary authorities and, more recently, from economic researchers. So we thought, through our research paper, to highlight how inflationary pressures affect, in particular, Algeria's public spending policy. In order to find out, we have relied on the descriptive approach to defining the concepts of inflation as well as public expenditure, on the analytical approach to understanding the causes of inflationary pressures in Algeria and on the standard approach using the spss programme, through which we have concluded that there is a strong relationship between public spending and both the monetary mass and inflation rates, that is, changes in the monetary mass and inflation rates directly affect changes in public spending.
The Impact of inflationary pressures on public spending policy in Algeria in the period 2000-2019
Keywords: تضخم ; ضغوط تضخمية ; إنفاق عام